Implementasi dan Tantangan Akad Musyarakah dalam Pembiayaan Syariah di Indonesia: Analisis Regulasi, Praktik, dan Strategi Optimalisasi - Rahmi, Nispan; Rizali, Muhammad; Badrian, Badrian (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2025)
This study aims to analyze the implementation of Musyarakah contracts in Islamic finance in Indonesia, identify the key challenges in its application, and explore strategies for optimizing this scheme. The research employs a qualitative approach by analyzing regulations, fatwas, and case studies of Musyarakah implementation in several Islamic financial institutions. The results indicate that optimizing Musyarakah contracts depends on the reformulation of more comprehensive policies, including revisions to Law No. 21/2008, improvements in DSN-MUI fatwas, and more detailed OJK guidelines. Enhancing information transparency and strengthening monitoring systems are strategic steps in risk mitigation. Additionally, public education on the concept and benefits of Musyarakah needs to be expanded to increase awareness and trust in this financing instrument.